Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

how do i simplify this equation using boolean algebra:

AB + ¬AC + BC

to be equal to

AB + ¬AC

the BC is unneeded, but how do i remove that term using boolean algebra?

share|cite|improve this question

$$\begin{align*} AB+\lnot AC+BC&=AB+\lnot AC+(A+\lnot A)BC\\ &=AB+\lnot AC+ABC+\lnot ABC\\ &=(AB+ABC)+(\lnot AC+\lnot ACB)\\ &=AB+\lnot AC \end{align*}$$

share|cite|improve this answer

We have: $$ A + \lnot A = 1 $$

And: $$ BC = 1 \cdot BC = (A + \lnot A)BC = ABC + \lnot ABC $$

Plug into your expression to get: \begin{align*} AB + \lnot AC + BC &= AB + \lnot AC + (ABC + \lnot ABC) \\ &= (AB + ABC) + (\lnot AC + \lnot ABC) \\ &= \left(AB + (AB)C\right) + \left(\lnot AC + (\lnot AC)B\right) \\ &= AB + \lnot AC \end{align*}

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.